2018
DOI: 10.1016/j.cbpc.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Manganese toxicity is targeting an early step in the dopamine signal transduction pathway that controls lateral cilia activity in the bivalve mollusc Crassostrea virginica

Abstract: Manganese is a neurotoxin causing manganism, a Parkinson-like clinical disorder. Manganese has been shown to interfere with dopaminergic neurotransmission, but the neurotoxic mechanism involved is not fully resolved. In the bivalve mollusc Crassostrea virginica also known as the eastern oyster, beating rates of lateral cilia of the gill are controlled by dopaminergic-serotonergic innervation originating from their cerebral and visceral ganglia. Terminal release of dopamine activates D2-like receptors on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Research has predominantly focused on DA subtype 2 receptor (D2R) and the DA transporter (DAT) responsible for Mn transport into DA neurons (100). Nelson et al showed that D2R are involved Mn toxicity, at the receptor level or at a point downstream in the signaling cascade that does not involve adenylyl cyclase (101). MnCl 2 exposure can lead to DA depletion and blunt the efficacy of DAergic neurotransmission leading to upregulation of the post-synaptic dopamine receptors and causing behavioral alterations including hypoactivity, cognitive impairments and altered sensorimotor function (102).…”
Section: Glutamatementioning
confidence: 99%
“…Research has predominantly focused on DA subtype 2 receptor (D2R) and the DA transporter (DAT) responsible for Mn transport into DA neurons (100). Nelson et al showed that D2R are involved Mn toxicity, at the receptor level or at a point downstream in the signaling cascade that does not involve adenylyl cyclase (101). MnCl 2 exposure can lead to DA depletion and blunt the efficacy of DAergic neurotransmission leading to upregulation of the post-synaptic dopamine receptors and causing behavioral alterations including hypoactivity, cognitive impairments and altered sensorimotor function (102).…”
Section: Glutamatementioning
confidence: 99%
“…Consequently, its input into the water runoff is expected to be enhanced. The biological effects of Cpz are associated with calcium homeostasis (Xu et al 2010 ) and manganese toxicity (Nelson et al 2018 ). The drug is known to interact with the cell membrane dynamin and block the clathrin-dependent endocytosis essential for the entry of coronavirus into the host cell (Plaze et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid pollution of water with heavy metals has become the most prevalent environmental concern. Heavy metals may alter the water surface as a result of industrial activities which produce polluting effluents that are discharged to the water surface. , Heavy metals have a high ability for persistence and can be transferred to various environmental components, such as soil, plants, food, and drinking water. Human exposure to heavy metals, even with very low traces, is considered hazardous due to the fact that heavy metal accumulation, over time, can lead to higher and dangerous concentrations, and the symptoms start to appear late in the human lifecycle. For example, manganese is considered as essential element for humans; however, the reported risk of manganese pollution is now reaching higher levels, especially among people who drink manganese-polluted water or those who work in mining and are exposed to air polluted with manganese through direct inhalation. The commonly reported health effects of excessive exposure to manganese include depression, changes in memory ability, as well as irritability and, in some cases, tremors. , Another example of a heavy metal pollutant is cobalt, which is an essential element at trace levels but is toxic at higher levels of exposure, leading to hematological effects as well as immune system disturbance. Lead is reported to have toxic effects on humans at high exposure levels in both children and adults. The symptoms include renal and degenerative effects as well as intellectual disabilities. There are many treatment methods for the remediation of heavy metals from wastewater, such as reverse osmosis, chemical precipitation, ion exchange, filtration, and adsorption. ,− …”
Section: Introductionmentioning
confidence: 99%
“… 12 14 The commonly reported health effects of excessive exposure to manganese include depression, changes in memory ability, as well as irritability and, in some cases, tremors. 15 , 16 Another example of a heavy metal pollutant is cobalt, which is an essential element at trace levels but is toxic at higher levels of exposure, leading to hematological effects as well as immune system disturbance. 17 − 20 Lead is reported to have toxic effects on humans at high exposure levels in both children and adults.…”
Section: Introductionmentioning
confidence: 99%